ANALYSIS OF THE INFLUENCE OF SERVICE QUALITY ON SHOPEE CUSTOMER SATISFACTION AND LOYALTY - Nurdin; Cipta Sigitta Hariyono, Rito (Yayasan Nuraini Ibrahim Mandiri, 2023)
The increasing use of shopee as an online sales stall with various features offered makes the background in this study. In addition, researchers observed that there are still some shopee users who complain about poor service quality such as very long delivery, product discrepancies that come, and require a strong enough internet connection to access shopee which makes it difficult for people who are in areas with minimal internet to use shopee. This study aims to determine the quality of service to customer satisfaction and customer loyalty of the Shopee application in the South Sumatra region. The research methods used are descriptive methods with quantitative approaches and data collection techniques using literature studies and questionnaires where the sample of this study is Shopee consumers specifically for the South Sumatra region and data analysis techniques using path analysis. The results of this study are that service quality has a significant effect on the variable of customer loyalty received with a contribution of 26%, service quality has a significant effect on the variable of customer satisfaction received with a contribution of 26%, customer loyalty has a significant effect on the variable of customer satisfaction received with a contribution of 21%. The hope is that this research can be a suggestion for shopee companies to develop according to what customers feel